Pengembangan Media Audiovisual Berbasis Kearifan Lokal pada Siswa Sekolah Dasar - Zainab, Zainab; Pirol, Abdul; Suryani, Lilis (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This research explores the needs analysis, design, validity, and practicality of audiovisual media focused on the theme "Beautiful Diversity in My Country" based on local wisdom at SDN 22 Murante. Using the R&D method with the ADDIE model, data were gathered through interviews, questionnaires, and tests, then analyzed qualitatively and quantitatively. The study involved 17 fourth-grade students. Findings suggest the ongoing learning process requires innovative audiovisual media addressing the theme. The designed media, associated with local tribal conditions, achieved a validity of 85.33%, signifying very high validity. Practicality, involving 17 students and a teacher, scored 89% and 97%, respectively, indicating high practicality.